Thermochemistry of stoichiometric rare earth oxyfluorides REOF. Issue 2 (27th September 2021) - Yang, Shuhao; Anderko, Andre; Riman, Richard E.; Navrotsky, Alexandra
Abstract: Rare earth oxyfluorides (REOF) have potential applications in luminescent devices and energy storage and are important for synthesis and properties of RE‐doped oxyfluoride glasses. This study evaluates the thermodynamic properties of stoichiometric REOF with varying RE (RE = La, Nd, Gd, Ho, Y, and Yb) elements using high temperature oxide melt solution calorimetry and investigates the phase transitions of YbOF by differential scanning calorimetry. The formation enthalpies from binary oxides and fluorides are exothermic and become less exothermic with the decrease of ionic radius of RE 3+, showing that REOF compounds are energetically stable relative to equal molar mixtures of RE2 O3 and REF3 and the RE–O interactions contribute to most of their thermodynamic stabilities. Different from REOF with large RE ions (La–Er and Y) having the rhombohedral phase, REOF with small cations (e.g., Yb) possesses the monoclinic structure as the more energetically stable phase at room temperature. However, the slow transition between the monoclinic and cubic phases easily generates the rhombohedral phase, which is favored by kinetics.